"The disenthralled hosts of freedom" : party prophecy in the antebellum editions of Leaves of grass - Grant, David, 1959 December 6- (Iowa Whitman series., 2021)
"Whitman wrote three distinct editions of Leaves of Grass before the civil war. During those years he was passionately committed to party anti-slavery, and his unpublished tract The Eighteenth Presidency shows that he was fully attuned to the kind of rhetoric coming out of the new Republican party. This study explores how the prophecies of the pre-war Leaves of Grass relate to the prophecy of this new party. It seeks not only to ground Whitman's work in that context but also to bring out features of party discourse that make it relevant to literary and cultural studies, not just to history or political science. Anti-slavery party discourse set itself the task of curing an ailing people who had grown compliant, inert, complacent, and numbed; it fashioned a complete fictional world where the people could be reactivated into assuming their true role in the republic. Both as a cause and a result of this rejuvenation, they would come into their own and spread their energies over the land and over the body politic, thereby rescuing their country, at the last minute, from what would otherwise be the permanent dominion of slavery. Party discourse had long hinged its success on such magical transformations of the people individually and collectively, and the anti-slavery cause therefore found the language of party a useful vehicle to express its narrative of national salvation. Whitman's celebrations of his nation's potential need to be seen in this context: like his party, he calls on the people to reject their own subordination and take command of the future. Through the speaker's complex meditations on and addresses to Americans, Leaves of Grass summons up the various powers that have lain dormant in the citizenry, confident that the people will channel them so as to redeem themselves as they also redeem the nation"--